2015
DOI: 10.1097/md.0000000000001984
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Surgery Against Early Subtalar Arthrodesis in Displaced Intra-articular Calcaneal Fractures

Abstract: The aim of this study is to determine whether surgery offers protection against early subtalar arthrodesis in displaced intraarticular calcaneal fractures.Systematic review and meta-analysis: searches of electronic databases 1980 to August 2014, checking of reference lists, hand searching of journals, and contact with experts. Randomized controlled trials (RCTs) in which surgical treatment was compared with nonsurgical treatment of displaced intra-articular calcaneal fractures from 1980 to 2014. The modified J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…[20][21][22] Surgical reduction of the articular surface has been demonstrated to reduce rates of subtalar arthritis compared to nonoperative management. 18 Baumgaertel and several other studies have demonstrated early external fixation as an effective mode for restoring calcaneal morphology, consistent with our experience. 4,23,24 Magnan et al argued that restoration of normal calcaneal architecture is more important than articular reduction and can be accomplished with external fixation alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[20][21][22] Surgical reduction of the articular surface has been demonstrated to reduce rates of subtalar arthritis compared to nonoperative management. 18 Baumgaertel and several other studies have demonstrated early external fixation as an effective mode for restoring calcaneal morphology, consistent with our experience. 4,23,24 Magnan et al argued that restoration of normal calcaneal architecture is more important than articular reduction and can be accomplished with external fixation alone.…”
Section: Discussionsupporting
confidence: 92%
“…[12][13][14][15][16][17] Benefits include improved clinical outcomes, reduced subtalar arthritis, and decreased need for complex secondary surgeries compared to nonoperative management. 18,19 When surgery is recommended, the two goals of treatment are (1) restoration of calcaneal morphology and (2) anatomic reduction of the involved articular surfaces. Restoring calcaneal morphology mitigates late problems associated with calcaneal malunion including anterior tibiotalar impingement, subfibular impingement, gait abnormality, and adjacent joint degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…But a basic conclusion supported by certain randomized controlled trials (RCTs) [ 4 , 5 ] and even many meta-analysis [ 6 8 ] has been drawn that surgical treatment can better reconstruct the anatomy of the calcaneus but bring a higher incidence of complications compared with the nonsurgical treatment. Surgical treatment can also lower the subtalar fusion rate and offer protection against early subtalar arthrodesis in DIACFs [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all studies cite insufficient evidence to make a recommendation. Others like Zhang et al [ 16 ], Luo et al [ 17 ] and Liu et al [ 18 ] have stated that surgical interventions in the hands of experienced surgeons have better outcomes and less subtalar fusions are subsequently required.…”
Section: Operative Versus Nonoperative Treatmentmentioning
confidence: 99%
“… Insufficient evidence for recommendations. Liu et al 2015 [ 18 ] 966 patients. Surgery protects against subtalar arthrodesis.…”
Section: Operative Versus Nonoperative Treatmentmentioning
confidence: 99%